BRAF Inhibitor Therapy‐Related Encephalitis in a Patient with Metastatic Melanoma. (17th July 2021) - Babacan, Nalan Akgul; Peguero, Edwin; Forsyth, Peter; Eroglu, Zeynep
Abstract: Introduction: BRAF inhibitors such as encorafenib and vemurafenib in combination with MEK inhibitors are commonly used for the treatment of patients with BRAF V600–mutant melanoma. Case Presentation: A patient with relapsed metastatic melanoma with a BRAF V600 mutation was started on treatment with vemurafenib and cobimetinib. Within 2 weeks of treatment start, he was hospitalized and diagnosed with encephalitis through a lumbar puncture and treated with corticosteroids, with subsequent normalization of cerebrospinal fluid (CSF) findings. When he recovered and was switched to encorafenib treatment, the same symptoms recurred, and the patient was treated with high‐dose steroids and intravenous immunoglobulin, again with improvement in his CSF. He has not had a relapse of his symptoms since BRAF inhibitor treatment was permanently discontinued. Conclusion: This is the first known report of a patient who has developed encephalitis because of treatment with BRAF inhibitors. Abstract : This article reports the first known case of a patient who developed encephalitis because of treatment with BRAF inhibitors.